PENGARUH KECERDASAN EMOSIONAL DAN IKLIM BELAJAR TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS V DI SD NEGERI 06 TANJUNG AMAN - Fara Diba Kofa; Muhammad Nurwahidin; Miranda Abung; Sowiyah (STKIP Subang, 2026)
The problem addressed in this study was the low learning motivation of fifth-grade students at SD Negeri 06 Tanjung Aman. This study aimed to analyze the influence of emotional intelligence and the learning climate on students' learning motivation at the school. The study employed a quantitative approach using an ex post facto method. The data were collected by administering a Likert-scale questionnaire to all fifth-grade students as the respondents. The data was analyzed using multiple linear regression analysis. The results showed that, partially, emotional intelligence did not have a significant effect on learning motivation, whereas the learning climate had a significant effect on learning motivation. Simultaneously, emotional intelligence and the learning climate were found to have a significant effect on students' learning motivation, with the learning climate being the most dominant factor influencing learning motivation.